THE ANALYSIS OF IMAGERY IN WAR-THEMED POETRY BY WALT WHITMAN - Tribuana Tungga Dewi; Cita Hikmah Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the contribution of imagery to readers’ understanding of war realities in the poetry of Walt Whitman. Whitman’s war poems, particularly those written during and after the American Civil War, present vivid sensory details that transform abstract notions of heroism, suffering, and death into concrete and emotionally resonant experiences. Through visual, auditory, and tactile imagery, Whitman constructs realistic depictions of battlefield scenes, wounded soldiers, and psychological trauma, allowing readers to perceive war not as romanticized glory but as a human and physical tragedy. Using a qualitative textual analysis, this study explores how imagery functions as a literary device to bridge the gap between historical events and readers’ emotional engagement. The findings indicate that Whitman’s imagery enhances empathy, deepens comprehension of war’s brutality, and encourages critical reflection on the costs of conflict. Therefore, imagery plays a crucial role in shaping readers’ interpretations and in presenting war realities in an immediate and impactful manner.